2017
DOI: 10.1111/obr.12591
|View full text |Cite
|
Sign up to set email alerts
|

Can weight gain be prevented in women receiving treatment for breast cancer? A systematic review of intervention studies

Abstract: SummaryBackground: Obesity and weight gain have been associated with poor disease-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 61 publications
(162 reference statements)
0
37
0
7
Order By: Relevance
“…In the no weight gain group, 36% of women lost weight and 64% maintained body weight during oncological treatment. There were no statistical differences in systemic therapy duration [ 33.9% (95% CI 32.0-35.8), p = 0.91] between women in the weight gain group and no weight gain group during the oncological treatment, respectively ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the no weight gain group, 36% of women lost weight and 64% maintained body weight during oncological treatment. There were no statistical differences in systemic therapy duration [ 33.9% (95% CI 32.0-35.8), p = 0.91] between women in the weight gain group and no weight gain group during the oncological treatment, respectively ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have suggested that women should be advised to prevent weight gain during breast cancer treatment, even those with adequate body weight at the time of diagnosis 17 . Dietary recommendations include the intake of a micronutrient-rich diet, low in simple carbohydrates and total fats 32,33 . In addition to helping to prevent weight gain, regular physical activities may reduce common side effects of breast cancer therapy, such as fatigue, depression and decreased muscle strength 34 , since nutritional counseling alone in women who were undergoing treatment for breast cancer did not prevent weight gain 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Promising evidence suggested that weight gain may be prevented in EBC patients with diet intervention, achieving weight maintenance or loss [32,33]. The educational component of our intervention was based on international recommendations, promoting the Med-Diet, not using group educational sessions [34].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the importance of knowing, besides weight and BMI, the body composition of these patients becomes clear, given the evidence of a change in body composition after the diagnosis and treatment of breast cancer, with increased adipose tissue and reduced lean tissue, leading to the development of sarcopenic obesity 25 . Women evaluated in this study presented reduced lean mass and increased fat mass after cancer treatment, corroborating the results by Cisneros et al 26 , in which women with the same cancer diagnosis had increased fat mass and reduced lean mass after chemotherapy.…”
Section: Discussionmentioning
confidence: 99%